2012
DOI: 10.3390/ijms13021790
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidative Damage on Cisplatin Exposure and Alterations in Antioxidant Defense System in Rat Kidneys: A Possible Protective Effect of Selenium

Abstract: Cisplatin (Cis-diamminedichloroplatinum II, CP) is an important chemotherapeutic agent, useful in the treatment of several cancers, but with several side effects such as nephrotoxicity. The present study investigated the possible protective effect of selenium (Se) against CP-induced oxidative stress in the rat kidneys. Male Wistar albino rats were injected with a single dose of cisplatin (7 mg CP/kg b.m., i.p.) and selenium (6 mg Se/kg b.m, as Na2SeO3, i.p.), alone or in combination. The obtained results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 54 publications
8
52
0
2
Order By: Relevance
“…Owing to the reports by Ognjanovic et al [37] and Ohnishi et al [38] they addressed the same findings as in our study [36,37,39].…”
Section: Discussionsupporting
confidence: 72%
“…Owing to the reports by Ognjanovic et al [37] and Ohnishi et al [38] they addressed the same findings as in our study [36,37,39].…”
Section: Discussionsupporting
confidence: 72%
“…Two groups were intraperitoneally injected with a single dose of cisplatin (CDDP) at 6.5 mg/kg body weight. 41 CDDP was suspended in 10 ml/kg 1% methyl cellulose. One of the groups injected with CDDP was subsequently treated with vehicle (C) or CV at 3 ml/kg body weight, p.o.…”
Section: Protocol Of the Studymentioning
confidence: 99%
“…Elevation of GSH levels has been shown to increase the resistance of cancer cells to cisplatin (Meijer et al, 1990;Kartalou and Essigmann, 2001), while depletion of GSH levels could potentiate the cytotoxicity of a variety of antitumor agents (Arrick and Nathan, 1984). Several investigators have demonstrated that cisplatin induces ROS primarily by decreasing the activity of antioxidant enzymes and by depleting intracellular concentrations of GSH (Husain et al, 1998;Ognjanovic et al, 2012). Depletion in the renal GSH level in rats has also been reported in response to oxidative stress caused by cisplatin treatment (Silva et al, 2001).…”
Section: Discussionmentioning
confidence: 99%